Efeito de um programa de treinamento auditivo na redução do incômodo com o zumbido e nas habilidades auditivas - Bertuol, Bianca (2017)
Tinnitus causes distinct reactions in individual that have this complaint. This symptom comes from an involvement of somewhere portion in the auditory pathway, either peripheral or central. Hearing loss, such as sensory deprivation, is a possible cause of tinnitus appearance. Auditory Training, based on auditory neuroplasticity, is able to reorganize the auditory pathway and can be a possible form for tinnitus treatment. The objective of this research was to measure the effects of an Auditory Training modality on tinnitus and auditory abilities in elderly people with hearing loss, and also using hearing aids. The elderly ones (n=190) were contacted from an initial selection in the Hearing Aids Laboratory of one Speech Language Pathology and Audiology Service. Sample was composed of individuals older than 60 years, with tinnitus (at least 6 months), hearing loss degree to moderate, and leastwise one auditory ability with alteration, using hearing aids. The procedure battery was composed by: Anamnesis, Tinnitus Handicap Inventory, Basic Audiological Assessment, Acuphenometry, Auditory processing tests (Randon Gap Detection Test, : Speech Test with White Noise and Dichotic Test of Digits), electrophysiological evaluation of auditory processing (P300) and psychological evaluation. After the initial assessments, the sample arrangement was composed of five elderly, they perfomed the Auditory Training Acoustically Controlled Computerized, using the software Escuta Ativa (Active Listening), which was conducted by 16 session on average 30 minutes each. After the proposed treatment, the elderly had 20 days of rest and so were reassessed with the same battery procedures. Wilcoxon's test was used to compare the two periods, pre- and post-treatment. The significance level was 0.10 because of the reduced sample, the confidence intervals were 95%. The elderly presented a statistically significant difference in the pre- and post-treatment period in relation to tinnitus severity as measured by the Tinnitus Handicap Inventory (Value of p = 0.043 *) and auditory processing behavioral tests: Speech Test with White Noise P = 0.043 * for both ears) and Dichotic Test of Digits (p value OD = 0.043 *, p value OE = 0.068 *). It was not possible to observe relevant electrophysiological changes in long-latency auditory evoked potential. The results obtained in this dissertation were divided into scientific articles; one of them is in this work.